Impact of adherence to key performance indicators on mortality among patients managed for ischemic stroke - Mustapha Mohammed; Hadzliana Zainal; Balamurugan Tangiisuran; Sabariah N. Harun; Siti M. Ghadzi; Irene Looi; Norsima N. Sidek; Keng L. Yee; Zariah A. Aziz (Centro de Investigaciones y Publicaciones Farmaceuticas, 2020)
Background: Stroke is a leading cause of death worldwide. The cases of acute ischemic stroke are on the increase in the Asia Pacific, particularly in Malaysia. Various health organizations have recommended guidelines for managing ischemic stroke, but adherence to key performance indicators (KPI) from the guidelines and impact on patient outcomes, particularly mortality, are rarely explored. Objective: This study aims to evaluate the impact of adherence to key performance indicators on mortality among patients managed for ischemic stroke. Methods: We included all first-ever ischemic stroke patients enrolled in the multiethnic Malaysian National Neurology Registry (NNeuR) - a prospective cohort study and followed-up for six months. Patients' baseline clinical characteristics, risk factors, neurological findings, treatments, KPI and mortality outcome were evaluated. The KPI nonadherence (NAR) and relationship with mortality were evaluated. NAR>25% threshold was considered suboptimal. Results: A total of 579 first-ever ischemic stroke patients were included in the final analysis. The overall mortality was recorded as 23 (4.0%) in six months, with a median (interquartile) age of 65 (20) years. Majority of the patients (dead or alive) had partial anterior circulation infarct, PACI (43.5%; 34.0%) and total anterior circulation infarct, TACI (26.1%; 8.8%). In addition, DVT prophylaxis (82.8%), anticoagulant for atrial fibrillation (AF) patients (48.8%) and rehabilitation (26.2%) were considered suboptimal. NAR < 2 was significantly associated with a decrease in mortality (odds ratio 0.16; 0.02-0.12) compared to NAR>2. Survival analysis showed that death is more likely in patients with NAR>2 (p=0.05). Conclusions: KPI nonadherence was associated with mortality among ischemic stroke patients. The adherence to the KPI was sub-optimal, particularly in DVT prophylaxis, anticoagulant for AF patients and rehabilitation. These findings reflect the importance of continuous quality measurement and implementation of evidence recommendations in healthcare delivery to achieve optimal outcome among stroke patients.